The Correlation Between Students’ Habit In Writing Diary And Students Ability In Writing Recount Text - Mutiana Nurmalasari Budiman (Jurnal Pembangunan dan Kebijakan Publik, 2019)
The research entitled “The Correlation between Students’ Habit in Writing Diary and Students’ Ability in Writing Recount Text”. It was aimed to find out the significant correlation between students’ habit in writing diary and students’ ability in writing recount text. Quantitative method was used to find out the correlation between two variables. To find out the significant correlation between students’ habit in writing diary and students’ ability in writing recount text, this paper used ex post facto. The data of writing recount text result was counted with Pearson Product Momment. The result of Pearson test showed tobserved was 0.17and ttable was 2.1604. The writer used significant value 5% or 0.05. It means that H0 was accepted and Ha was rejected. Based on the result of Pearson Product Momment, there were no significant correlation between students’ habit in writing diary and students’ ability in writing recount text.